Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Keputusan Penggunaan Pay-Later - Ayu Febrianti; Adria Wuri Lastari; Evrina (ARZUSIN, 2026)
The use of pay-later services among university students continues to increase, but research integrating financial literacy and lifestyle in explaining decisions to use these services remains limited. This study aimed to analyze the effects of financial literacy and lifestyle on decisions to use pay-later services among students of the Management Study Program, Faculty of Economics, Universitas Adiwangsa Jambi. The study employed a quantitative approach with a causal-associative design. The research sample consisted of 55 students selected through purposive sampling based on the criteria of being active students who were aware of or had previously used pay-later services. Data were collected using a Likert-scale questionnaire and analyzed through Partial Least Squares–Structural Equation Modeling with the assistance of SmartPLS. The results showed that financial literacy had a positive and significant effect on decisions to use pay-later services (β = 0.305; p = 0.003). Lifestyle also had a positive and significant effect on decisions to use pay-later services (β = 0.502; p < 0.001) and was the more dominant factor. Financial literacy and lifestyle jointly explained 52.3% of the variation in decisions to use pay-later services. These findings strengthen the application of the Theory of Planned Behavior in the context of digital financing and confirm that decisions to use pay-later services are influenced not only by the ability to understand financial matters but also by students’ consumption patterns. Practically, higher education institutions need to develop digital financial literacy programs accompanied by efforts to strengthen students’ ability to control consumptive behavior. Future studies are recommended to examine the roles of self-control, income, promotion, and social influence in explaining decisions to use pay-later services. Keywords: Financial Literacy; Lifestyle; Usage Decision; Pay-Later; University Students